2018
DOI: 10.3390/biomedicines6020041
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Acute Phase Liver Graft Injury in Liver Transplantation

Abstract: Background: Liver transplantation remains the treatment of choice for a selected group of hepatocellular carcinoma (HCC) patients. However, the long-term benefit is greatly hampered by post-transplant HCC recurrence. Our previous studies have identified liver graft injury as an acute phase event leading to post-transplant tumor recurrence. Methods: To re-examine this acute phase event at the molecular level and in an unbiased way, RNA sequencing (RNA-Seq) was performed on liver graft biopsies obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Multivariate Cox Regression analysis of the signi cant predictors of disease-free survival showed that there was no a signi cantly independent predictor de ned ( Table 3), suggesting that these predictors dependently in uenced the disease-free survival of HCC recipients. These above ndings agreed with our previous study that early phase injury-induced molecules play in uential roles in late phase HCC recurrence after liver transplantation (14). Altogether, our results indicated that EPC GSTA2…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Multivariate Cox Regression analysis of the signi cant predictors of disease-free survival showed that there was no a signi cantly independent predictor de ned ( Table 3), suggesting that these predictors dependently in uenced the disease-free survival of HCC recipients. These above ndings agreed with our previous study that early phase injury-induced molecules play in uential roles in late phase HCC recurrence after liver transplantation (14). Altogether, our results indicated that EPC GSTA2…”
Section: Discussionsupporting
confidence: 93%
“…Identi cation of GSTA2 as a HCC-recurrence associated gene at early-phase after liver transplantation RNA sequencing was previously performed on liver biopsies collected from early phase after liver transplantation (2 hours after portal vein reperfusion) (14). To identify differentially expressed earlyphase genes associated with late-phase HCC recurrence, the transcription pro le of the liver biopsies from the recurrent recipients (N = 6) was compared to the non-recurrent recipients (N = 5) through a one-by-one comparison approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While liver transplantation is a potentially curative treatment of hepatocellular carcinoma, liver graft injury has been identified as an acute phase event that leads to post-transplant tumor recurrence. Lee et al examined this acute phase event at the molecular level by transcriptomic analysis of liver grafts from recipients with or without tumor recurrence following liver transplantation [21]. This study reveals the altered genetic expression in liver grafts, and paves the way to identify key molecular pathways that may be involved in post-transplant tumor recurrence.…”
Section: Biomarkers and Targets In Cancer Of Digestive Organsmentioning
confidence: 99%